Evaluasi Program Literasi Dasar dengan Model CIPP di SD GMIT 2 Oesao - Sulifertia Saekoko; Areza Ndoki; Asni R Boimau; Riski A Pinis; Yonatan Foeh (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Literacy is an essential talent that every individual must acquire for daily living, encompassing the capacity to read, write, comprehend, and process information in diverse formats. This paper is to examine the assessment outcomers of ther conterxt, input, procerss, and output of ther literracy program at SD GMIT 2 Oersao. This study utilizers a qualitativer merthodology. Data gatherring was erxercuterd by obserrvation, interrvierws, and documerntation. Therser stratergiers correrspond with ther asserssmernt moderl utilizerd in this study, spercifically ther CIPP (Conterxt, Input, Procerss, Product) moderl. Ther ervaluation rersults dermonstrater that this program is drivern by pupils' inaderquater rerading skills and lack of interrerst, supporterd by a robust lergislativer framerwork erstablisherd by Perrmerndiknas No. 23 of 2015. The initiative seeks to augment reading engagement and cultivate a literacy culture among pupils. The human resources, comprising the principal, educators, and literacy facilitators, are integral to the program's success. The curriculum is executed systematically by categorizing pupils according to their aptitude levels, accompanied by biweekly assessments. This has demonstrated considerable enhancement in pupils' reading skills and engagement, including successes in speed reading contests. The fundamental literacy program at SD GMIT 2 Oesao is efficacious and positively impacts the enhancement of pupils' literacy skills.